ANALISIS MINERAL TANAH DAN KONDISI GEOLOGI TERHADAP PRODUKTIFITAS PERTANIAN DI DESA TAMAILA UTARA - Podungge, Yulin; Mamangkay, Bambang (Jurnal Biogenerasi, 2024)
Soil quality is an important factor in determining agricultural yields, and geological conditions also influence the availability and distribution of essential minerals for plant growth. Tamaila Utara Village, in Gorontalo Regency, has significant agricultural potential, but it has not been fully optimized. The objective of this study is to conduct an in-depth analysis of soil mineral content and geological conditions, as well as their impact on agricultural productivity. This study uses a combined approach of laboratory analysis and quantitative analysis with the Guttman method. Soil samples were collected at several agricultural sites, based on land slope, followed by an analysis of macro and micro-nutrient content. The results show that the volcanic rock-based geological conditions, rich in minerals, support the availability of nutrients in several areas. However, the farming practices for corn in Tamaila Utara Village are still unsustainable, as these activities have significantly impacted the surrounding ecosystem, soil quality, and corn yields, which have declined over the past three years.